Conrad’s Efficiency in An Outpost of Progress - Ariesta, Daisy; Mau, Emanuella Christine Natalia (Universitas Sanata Dharma, 2018)
This study aims at finding out Conrad’s efficiency in An Outpost of Progress. The efficiency itself means the characteristic of being human which is found in Conrad’s An Outpost of Progress that is directed on how white people should act. The main character of this story is analyzed using the theory of character The theory of author and voice is used to crosscheck the findings in theory of characters. These theories contribute to find out Conrad’s voice in the story.This study finds out that Conrad is emphasizing the importance of efficiency to white men. This study also supports Achebe’s statement toward Conrad being a racist. It is because Conrad is proud of having the efficiency and is looking down at the other race. Keywords: Efficiency, Joseph Conrad, Outpost of Progress